Acute effects of JUUL and IQOS in cigarette smokers. Issue 4 (10th February 2020) - Maloney, Sarah; Eversole, Alisha; Crabtree, Melanie; Soule, Eric; Eissenberg, Thomas; Breland, Alison
Abstract : Background: JUUL is an electronic cigarette that aerosolises a nicotine-containing liquid, while IQOS heats tobacco to produce an aerosol. Both are marketed to smokers, but their effects have seldom been examined in this population. Methods: Eighteen cigarette smokers (13 men) with no JUUL or IQOS experience completed a within-subject, laboratory study assessing nicotine delivery and subjective effects after controlled (10 puffs, 30 s interpuff interval) and ad libitum (90 min) use of JUUL, IQOS or own-brand (OB) cigarettes. Results: JUUL increased mean plasma nicotine concentration significantly from 2.2 (SD=0.7) ng/mL to 9.8 (4.9) ng/mL after 10 puffs and to 11.5 (9.3) ng/mL after ad libitum use. IQOS increased mean plasma nicotine significantly from 2.1 (0.2) ng/mL to 12.7 (6.2) ng/mL after 10 puffs and to 11.3 (8.0) ng/mL after ad libitum use. OB increased mean plasma nicotine significantly from 2.1 (0.2) ng/mL to 20.4 (11.4) ng/mL after 10 puffs and to 21.0 (10.2) ng/mL after ad libitum use. Mean OB plasma nicotine concentration was significantly higher than JUUL and IQOS. OB increased expired carbon monoxide concentration, but IQOS and JUUL did not. 'Craving a cigarette/nicotine' and 'Urges to smoke' were reduced significantly for all products following the directed bout. Conclusions: Among smokers, JUUL and IQOS delivered less nicotine than cigarettes. Also, in this sample, IQOS and OB reduced abstinence symptoms more effectively than JUUL. Additional work with experienced JUUL and IQOS users is needed, as their nicotine delivery profiles and subjective experiences may differ.